Addictions Causing Head-and-Neck Cancers (Indian Journal of Medical and Paediatric Oncology, 2020)
Head-and-neck cancers pose a serious economic burden, with most countries investing significant resources to reduce the incidence, primarily focusing on understanding addictive etiologies. The traditional literature focused on tobacco and alcohol use, with few studies on contemporary factors such as e-cigarette, waterpipe smoking, and human papillomavirus. This article attempts to collate and present an update on the globally identified etiologic factors.The aim of this study was to identify and review the addictive etiologic factors causing head-and-neck cancers.An electronic search was performed on Medline, Embase, and Google Scholar to identify the etiologies causing head-and-neck cancers and narrowed down on those driven by addiction. Further, we identified their constituents, mechanism of action, and the risks attributable to various forms of products.Substances identified included smoked and chewed tobacco, alcohol, mate, marijuana, areca nut and betel quid, and viruses. An alarming majority of youth are now utilizing these substances. Furthermore, migrant movements have led to the spread of traditional practices across the regions, especially from the Asian subcontinent.Ironically, despite modern advances and technology, we still see that a large proportion of population succumb to these cancers, emphasizing the need for more effective and targeted policies to combat this menace at the grassroots level.
Keywords: Addictions; alcohol; areca nut; betel quid; head-and-neck cancer; marijuana; tobacco; virus